Objectivity a very short introduction - Gaukroger, Stephen 1950-2023 (Very short introductions, 2012)
This title explores the theoretical and practical problems of objectivity by assessing the basic questions raised by it. Is objectivity possible? Can there be objectivity in matters of morals, or tastes? Objectivity is both an essential and elusive philosophical concept. An account is considered to be objective if it attempts to capture the nature of the object studied without judgement of a conscious entity or subject